2020
DOI: 10.1042/bcj20200444
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a special dicistronic transcription unit encoding histone methyltransferase su(var)3-9 and translation regulator eIF2γ in Tribolium castaneum

Abstract: Operons are rare in eukaryotes, where they often allow concerted expression of functionally related genes. While a dicistronic transcription unit encoding two unrelated genes, the suppressor of position-effect variegation su(var)3-9 and the gamma subunit of eukaryotic translation initiation factor 2 (eIF2γ) has been found in insecta, and its significance is not well understood. Here, we analyzed the evolutionary history of this transcription unit in arthropods and its functions by using model Coleoptera insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The supernatant was dried and suspended with 0.2 mL methanol. The 20E titer was measured using a Xevo TQ‐XS benchtop tandem quadrupole mass spectrometer (Waters, Milford, MA, USA) (Song et al ., 2020) and analyzed as previously described (Hikiba et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was dried and suspended with 0.2 mL methanol. The 20E titer was measured using a Xevo TQ‐XS benchtop tandem quadrupole mass spectrometer (Waters, Milford, MA, USA) (Song et al ., 2020) and analyzed as previously described (Hikiba et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Exogenous 20E treatment could partially rescue the metamorphosis deficiency due to inhibition of 20E pathway in Drosophila (Enya et al, 2014) and T. castaneum (Lin et al, 2018; Song, Pei, et al, 2020; Song, Zhong, et al, 2020). Similarly, our results showed that the molting rate of 20E injected group was higher than that of the control group (Figure 9a).…”
Section: Discussionmentioning
confidence: 99%